UZLUKSIZ MALAKA OSHIRISH TIZIMINI TASHKIL QILISHNING ILMIY-USLUBIY JIHATLARI - Pulotov Abdurayim Murotovich (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2020)
In this article are considering the scientific and methodological aspects of digital management of public education staff professional development system. Some aspects of modern pedagogical and digital technologies, new forms and methods of teaching, using the modern assessment methods in training processes are presented